Isolation and structure elucidation of phenolic antioxidants from Tamarind (Tamarindus indica L.) seeds and pericarp - Sudjaroen, Yuttana; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut; Owen, Robert (Food and chemical toxicology, 2005)
Although it is already known that Tamarind (Tamarindus indica L.) seeds contain phenolic substances, the individual components of the seeds have not been fully identified and quantitated, and in the case of Tamarind pericarp not reported. Therefore, major polyphenolic compounds were extracted using organic solvents and the metabolites were isolated by semi-preparative high performance liquid chromatography. Their structures were elucidated by liquid chromatography-electrospray-ionisation-mass spectrometry (LC-ESI-MS), nano-electrospray-ionisation mass spectrometry (ESI-MS), and where possible by gas chromatography-mass spectrometry (GC-MS) and 1H and 13C NMR. Quantitative analysis of polyphenolic compounds in Tamarind seeds and pericarp was conducted by analytical high performance liquid chromatography (HPLC), calculated against standard curves of authentic compounds. The yields of total phenolic compounds after Soxhlet extraction with methanol were 6.54 and 2.82g/kg (dry weight) in the seeds and pericarp respectively. The profile (%) of polyphenolics in Tamarind pericarp was dominated by proanthcyanidins (73.4) in various forms (+)-catechin (2.0), procyanidin B2 (8.2), (−)-epicatechin (9.4), procyanidin trimer (11.3), procyanidin tetramer (22.2), procyanidin pentamer (11.6), procyanidin hexamer (12.8) along with taxifolin (7.4), apigenin (2.0), eriodictyol (6.9), luteolin (5.0) and naringenin (1.4) of total phenols, respectively. The content of Tamarind seeds comprised only procyanidins, represented (%) mainly by oligomeric procyanidin tetramer (30.2), procyanidin hexamer (23.8), procyanidin trimer (18.1), procyanidin pentamer (17.6) with lower amounts of procyanidin B2 (5.5) and (−)-epicatechin (4.8). Extraction of Tamarind pericarp and seeds using acetone:methanol:acetic acid gave only procyanidin oligomers, but in much higher yield and variety. The antioxidant capacities of the Soxhlet methanolic extracts were determined, and indicates that Tamarind may be an important source of cancer chemopreventive natural products in tropical regions.